Implementation of a sales monitoring system for pathfnder travel network Ltd. - Mahbubuzzaman, S. M. (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.